Ehlers-Danlos syndrome/Accidental bruising. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2014)
After the first six months the child moves more and therefore accidental bruising is more frequent. However, bruising is also a clinical sign of Ehler-Danlos syndrome. This is why a differential diagnosis between the two conditions is necessary.